Transcutaneous measurement of bilirubin in Turkish newborns: comparison with total serum bilirubin - Kaynak-Türkmen, Münevver; Aydoğdu, S Ayvaz; Gökbulut, Cengiz; Yenisey, Ciğdem; Söz, Omer; Cetinkaya-Cakmak, Bilin (The Turkish Journal of Pediatrics, 2011)
Routine use of transcutaneous bilirubin (TcB) measurement in the newborn nursery could reduce costs, readmission rates for hyperbilirubinemia and the need for total serum bilirubin (TSB) measurements. The aim of this study was to examine the correlation between TcB measurement, as performed using BiliCheck, and TSB, measured with high-pressure liquid chromatography (HPLC) and with standard laboratory methods, and to determine the TcB cutoff points with desirable sensitivity and specificity values for various clinically relevant TSB levels by HPLC. Fifty-four infants of > or = 30 weeks of gestational age were enrolled in the study. Near simultaneous blood collection for TSB analysis by three methods--bedside bilirubinometer, diazo method and HPLC--and TcB measurement were performed. There was good correlation between TcB and HPLC-bilirubin (B) (r = 0.85), TSB by bilirubinometer and HPLC-B (r = 0.91) and TSB by diazo method and HPLC-B (r = 0.91). The cut-off limits providing a sensitivity of 100% for TcB measurements were TcB > or = 9 mg/dl for HPLC-B > 17 mg/dl and TcB > or = 8 mg/dl for HPLC-B > 15 mg/dl and HPLC-B > 13 mg/dl. Despite having good correlation with HPLC, BiliCheck showed worse performance than bilirubinometer and diazo method at various clinically relevant cut-off values. Since BiliCheck required relatively lower thresholds with false-positive results for having a sensitivity of 100%, it cannot be recommended as a complete substitute for serum bilirubin measurements.